A trade-off between solubility enhancement and physical stability upon simultaneous amorphization and nanonization of curcumin in comparison to amorphization alone - Wong, Jerome Jie Long (2018)
The numerous health benefits of curcumin (CUR) have not been fully realized due to its low aqueous solubility, resulting in poor bioavailability. While amorphization of CUR via amorphous solid dispersion (ASD) represents a well-established CUR solubility enhancement strategy, simultaneous amorphization and nanonization of CUR via amorphous CUR nanoparticles (or nano-CUR in short) have emerged only recently as the plausibly superior alternative to ASD. Herein we examined for the first time the amorphous nano-CUR versus the ASD of CUR in terms of their (1) in vitro solubility enhancement capability and (2) long-term physical stability. The ASD of CUR was prepared by spray drying with hydroxypropylmethylcellulose (HPMC) acting as crystallization inhibitor. The amorphous nano-CUR was investigated in both its (i) aqueous suspension and (ii) dry-powder forms in which the latter was prepared by spray drying with adjuvants (i.e. HPMC, trehalose, and soy lecithin). The results showed that the amorphous nano-CUR (in both its aqueous suspension and dry-powder forms) exhibited superior solubility enhancement to the ASD of CUR attributed to its faster dissolution rates. This was despite the ASD formulation contained a larger amount of HPMC. The superior solubility enhancement, however, came at the expense of low physical stability, where the amorphous nano-CUR showed signs of transformation to crystalline after three-month accelerated storage, which was not observed with the ASD. Thus, despite its inferior solubility enhancement, the conventional ASD of CUR was found to represent the more feasible CUR solubility enhancement strategy.